The use of stinging nettle tea (Urtica sp.) to control Aulacorthum solani and Macrosiphum euphorbiae on Ranunculus asiaticus - Wulf Florian; Podhorna Jana; Bandte Martina; Büttner Carmen; Rybak Malgorzata (Folia Horticulturae, 2023)
Natural and environmental-friendly approaches to control pests and diseases in horticultural production systems are showing an increasing trend. Biological alternatives, such as botanical extracts and basic substances, show promise in the reduction of the necessity for conventional plant protectants. In ornamentals, less is known about the usage, behaviour and potential of botanicals and basic substances for plant protection. In two trials, we investigated the effect of a weekly foliar spray of an aqueous extract of nettle (Urtica sp.; dried material 15 g · L–1) on two aphids, Macrosiphum euphorbiae and Aulacorthum solani. Experiments were conducted in the greenhouse with Ranunculus asiaticus as hostplant. The Urtica tea and azadirachtin (NeemAzal-T/S) as a standard used in common horticultural production were compared with the water control. Both previously infested and noninfested plants were built up to examine the effect on aphid population growth and migration. As a result, we showed that both treatments, Urtica tea and azadirachtin, reduce the aphid density significantly in comparison with the water control, although the effect of the Urtica tea was not as substantial as that of azadirachtin. Contrarily, treatments could not prevent aphid migration on previously noninfested plants. The study demonstrates that the basic substance Urtica tea can be suitable for the reduction of aphid pests in ornamental plant production, and thus, reduce the amount of synthetic plant protectants in horticulture.